Wilms Tumor Gene 1 (WT1) is a Prognostic Marker in High-Grade Uterine Sarcoma. Issue 2 (1st January 2011) - Coosemans, An; Van Calster, Ben; Verbist, Godelieve; Moerman, Philippe; Vergote, Ignace; Van Gool, Stefaan W.; Amant, Frédéric
Abstract : Introduction: Wilms tumor gene 1 ( WT1 ) contributes to uterine sarcoma tumor biology. In this study, we aimed to clarify the prognostic value of WT1. Methods: A retrospective clinical and histopathological review of 71 women with high-grade uterine sarcoma (leiomyosarcoma [n = 24], undifferentiated sarcoma [n = 9]), and carcinosarcoma (n = 38) was performed. Patients were followed up for at least 12 months. Wilms tumor gene 1 expression was determined by immunohistochemistry. Data on recurrence (progression-free survival) and overall survival (OS) were available for all patients. Univariate and multivariate analyses of WT1 expression were carried out using Kaplan-Meier curves and Cox regression, respectively. Results: Forty-nine (69%) tumors were WT1 positive. Forty-seven (66%) patients died of the disease, with a median OS time of 22 months. Wilms tumor gene 1 was a predictor of survival in the univariate analysis: the hazard ratio of WT1 positivity was 2.44 (95% confidence interval, 1.34-4.71) for progression-free survival and 2.48 (95% confidence interval, 1.26-4.90) for OS. Multivariate analysis including stage, age, tumor size, and sarcoma subtype identified only stage and WT1 positivity as independent prognostic markers for survival. Conclusions: The identification of WT1 as a prognostic marker confirms its role in high-grade uterine sarcoma and carcinosarcoma tumor biology.